Effects of Foil Bearing Load on Working Foil Wear - Bartosz MOCZULAK; Wojciech MIĄSKOWSKI; Igor DYBICH; Waldemar DUDDA (Problemy Mechatroniki)
The article presents issues related to the study on the impact of high-speed foil bearing service loads on the wear of working foils. The work includes a brief introduction, test methodology and a description of the test stand for testing the wear on working foil bearings under simulated operating conditions. The test stand was located in the Machinery Design Fundamentals laboratory at the Faculty of Technical Sciences of the University of Warmia and Mazury in Olsztyn (Poland), where it is used for start-stop tests. The article describes the course of the tests and the results, providing relevant conclusions and a better understanding of the phenomena occurring during work with foil bearings.